W 0 1, p(x) versus C 1 local minimizers for nonsmooth functionals - Che, Chengfu; Ge, Bin; Xue, Xiao-Ping; Zhou, Qing-Mei (Mathematical Modelling and Analysis, 2012)
In this paper, we study that the local minimizers of a class of functionals (not necessarily differentiable) in the C 1 -topology are still their local minimizers in